-19+13y=-6y

Simple and best practice solution for -19+13y=-6y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -19+13y=-6y equation:



-19+13y=-6y
We move all terms to the left:
-19+13y-(-6y)=0
We get rid of parentheses
13y+6y-19=0
We add all the numbers together, and all the variables
19y-19=0
We move all terms containing y to the left, all other terms to the right
19y=19
y=19/19
y=1

See similar equations:

| 5x-9+3x=55 | | 55x=1100 | | x(1/18+7/9)=300 | | 8m+15=55 | | -20-6s=-4s | | 3x-12+3x=7+6x-18 | | -9-2x=-3x | | 4x-2-5x-6=-12 | | 4x^2+8=9 | | 5x-3(4x-x)=-30-2x | | 4/5(15x+20-7x=5/6(12x-24)+6 | | 13+37=-5(3x-10) | | 9x-4=6x+20 | | 4(x+5)=2(x+27) | | -6j+5=17 | | 10+x3=1 | | 6j-2=70 | | 226=104-y | | x+3/x=92 | | 12r-12=8(r-1) | | (x-6)(x+3)=260 | | x/12-2=4 | | 3x-14/4=-4 | | 42=7x+6x-10 | | 15-3x/3=-6 | | (2x+6)=3(x+18 | | 467/8=21/4(b)+3/8(b-1) | | y-5/6y=13 | | 4x+2+82=10x+12 | | -2n+3n=-6 | | 4(2x+6)=3(x+18) | | C=5/4(k-80) |

Equations solver categories